Correlation between Current–Voltage Curves and Recombination Kinetics of Dye-Sensitized Solar Cells Investigated by the Galvanostatic Constant Intensity Light Perturbation Technique - Shi, YuShuai; Dong, XianDui (Journal of physical chemistry. C, 2013)
Correlation between current–voltage curves and recombination kinetics of dye-sensitized solar cells was a key subject for understanding the operation mechanisms and improving the device performance. A galvanostatic constant intensity light perturbation (GCILP) technique carried out on the current–voltage curve was developed to discover the correlation. The technique focused on synchronously deriving recombination kinetics and energetic distribution of trap state from the photovoltage responses and reconstructing the current–voltage curve by these derived kinetic parameters. In this technique, the photovoltage response amplitude was analyzed to obtain recombination kinetic parameters such as equilibrium dark recombination current density (or exchange current density) and recombination reaction order; the photovoltage response time trace was used to determine energetic distribution of trap states. Based on these analysis results, not only the effects of conduction band shifts and changes in the recombination rate on the open-circuit voltage could be analyzed but also the current–voltage curves could be successfully reconstructed. So this technique provided a new more convenient approach for efficiently evaluating and deeply understanding the important characteristics of solar cells.